A Study on the Novel ‘Lord of the Flies’: Exploring the Controversial Themes in Lord of the Flies (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Lord of the Fliesis a 1954 dystopian novel by Nobel Prize-winning English author WilliamGolding about a group of British boys stuck on an uninhabitedisland who try to govern themselves with disastrous results. Its stances onthe already controversial subjects of humannature and individual welfare versus the common goodearned it position 68 on the American Library Association’s list ofthe 100 most frequently challenged books of 1990–1999.[2]The novel is a reaction to the youth novel The Coral Island by R. M.Ballantyne.